Gender diversity on the board of directors and corporate risk: A behavioural agency theory perspective - Poletti-Hughes, Jannine; Briano-Turrent, Guadalupe C. (International review of financial analysis, 2019)
The benefit of gender diversity on the board of directors is a subject of current debate. We contribute to the literature on diversity and its impact on businesses from an analytical framework that incorporates agency theory and the concept of socioemotional wealth (SEW). Our findings suggest that the inclusion of women on the board goes beyond ethical concerns being also relevant from a business perspective (i.e. increases risk-taking). The proportion of independent female directors on the board is shown to increase venturing risk (i.e. with the expectation of improving future performance), but does not interfere with performance hazard risk which conceptualizes the family desire to preserve SEW, especially in firms where these risks are low. By contrast, the proportion of non-independent female directors on the board increases significantly performance hazard risk, but only in family firms. In summary, we find with data from Latin America that the motivation for risk-taking differs depending on whether the appointment is as an independent female director, the type of risk and on whether the firm is controlled by a family. •This paper emphasises the positive role of female independent directors to firms’ outcomes.•Firms with female directors assume more risk.•Non-independent female directors align their risk-taking to that of the family to preserve socio-emotional wealth.•Independent female directors motivate risk-taking on improving firm’s expected performance.